Performance Evaluation of Two Stages Parallel Flow Indirect Evaporative Cooling with Aspen Pads in Baghdad Climate Conditions (Journal of Engineering, 2024)
This study delves into the realm of advanced cooling techniques by examining the performance of a two-stage parallel flow indirect evaporative cooling system enhanced with aspen pads in the challenging climate of Baghdad. The objective was to achieve average air dry bulb temperatures (43 oC) below the ambient wet bulb temperatures (24.95 oC) with an average relative humidity of 23%, aiming for unparalleled cooling efficiency. The research experiment was carried out in the urban environment of Baghdad, characterized by high temperature conditions. The investigation focused on the potential of the two-stage parallel flow setup, combined with the cooling capability of aspen pads, to surpass the limitations imposed by conventional cooling methods. The empirical findings underscored the capacity of the two-stage parallel flow configuration to achieve air-dry bulb temperatures surpassing the ambient wet bulb temperature.Nonetheless, it was evident that an excessive application of water (exceeding 9 lpm) onto the aspen pads within the wet channels yielded adverse repercussions on the cooler's performance metrics, specifically in terms of wet bulb effectiveness and coefficient of performance. A range of air flows spanning from 150 CMH to 350 CMH was analyzed, revealing the influence of heightened air flow rates on the resultant dry bulb temperatures delivered by the cooling system. Notably, the peak wet-bulb effectiveness registered at 1.08, concurrently yielding a coefficient of performance measuring 7.8.